Computational Logic in Multi-Agent Systems 13th International Workshop, CLIMA XIII, Montpellier, France, August 27-28, 2012. Proceedings - Fisher, Michael; Torre, Leon.; Dastani, Mehdi; Governatori, Guido; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the proceedings of the 13th International Workshop on Computational Logic in Multi-Agent Systems, CLIMA XIII, held in Montpellier, France, in August 2012. The 11 regular papers were carefully reviewed and selected from 27 submissions and presented with three invited papers. The purpose of the CLIMA workshops is to provide a forum for discussing techniques, based on computational logic, for representing, programming and reasoning about agents and multi-agent systems in a formal way.
Bipolar Argumentation Frames and Contrary to Duty Obligations, Preliminary Report -- Multi-agent Only-Knowing -- Logics for Reasoning about Agents$1 (BAttitudes in Strategic Contexts -- A Time-Situated Meta-logic for Characterizing Goal-Processing Bounded Agents -- Distributed Defeasible Speculative Reasoning in Ambient Environment -- A Formal Semantics for Agent (Re)Organization -- Epistemic ATL with Perfect Recall, Past and Strategy Contexts -- Using Evolution Graphs for Describing Topology-Aware Prediction Models in Large Clusters -- Enhancing Goal-Based Requirements Consistency: An Argumentation-Based Approach -- A Game Theoretic Approach for Optimal Network Topologies in Opportunistic Networks -- MKNF Knowledge Bases in Multi-Context Systems -- Implementing Reversible Processes in Multi-agent Action Languages Using Answer Set Planning -- Full Hybrid (So(B-Calculus, Its Bisimulation Invariance and Application to Argumentation -- A Numerical Approach to the Merging of Argumentation Networks.s
Keywords: Computer science; Software engineering; Logic design; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Mathematical Logic and Formal Languages; Software Engineering; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs